FORENSIC EXAMINATION OF THE HANDWRITING CHARACTERISTICS OF ALCOHOLICS - Manjugouda R Patil, Dr.Channappa.F.Mulimani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
A forensic document examination normally consists of the comparison of naturally written questioned and request text to determine if they are of common authorship. Many times it is claimed that a particular document was not signed by the alleged person or if the signature was obtained, the person does not know of it because of intoxication. In these circumstances, two issues are to be decided i.e whether the person signed the document or not and if he has signed, was he under the influence of intoxication at that time. The first issue can be decided in a normal manner by the examination and comparison of the disputed and the known signatures of the person concerned to find out if the signature is in the handwriting of the same person. But the second issue is complicated and needs an exhaustive and thorough study. The variation in the handwriting may also depend on the level of education. As we all know that handwriting is arranged mentally and performed neuro-muscularly, it is affected by alcohol consumption and the consumption of drugs. The parameters of handwriting which reveals pronounced distinguish are word length, the height and width of an upper case, the height and width of a lower case, the height of ascending and descending letter, spacing between letters, number of tremor were all substantially increased. It is statistically confirmed that the transition in handwriting characteristics is due to the prompt of alcohol